Shattered : surviving the loss of a child - Roe, Gary (Healing Resources Publishing, 2017)
"Unthinkable. Unbelievable. Heartbreaking. Whatever words we choose, they all fall far short of the reality. The loss of a child is a terrible thing. How do we survive this? Can we? Shattered: Surviving the Loss of a Child was written to help."--Back cover.